1999
DOI: 10.1089/jwh.1.1999.8.1097
|View full text |Cite
|
Sign up to set email alerts
|

Women's Knowledge about Menopause, Hormone Replacement Therapy (HRT), and Interactions with Healthcare Providers: An Exploratory Study

Abstract: This community mail-based survey received responses from 665 women to questions in three areas: (1) sources of information about menopause, (2) knowledge of health risks associated with menopause, and (3) knowledge about hormone replacement therapy (HRT). Women received information from many sources, including healthcare providers, friends, and mothers, but the number one source of information about menopause was women's magazines (76%). Over half of women surveyed said they had left healthcare appointments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 8 publications
3
21
0
1
Order By: Relevance
“…Respondents' knowledge on health risks associated to menopause in this survey were similar to the other study (15). They were much more likely to identify osteoporosis rather than hypertension and heart diseases despite the fact that the risk of developing cardiovascular diseases is higher than osteoporosis (15).…”
Section: Discussionsupporting
confidence: 71%
“…Respondents' knowledge on health risks associated to menopause in this survey were similar to the other study (15). They were much more likely to identify osteoporosis rather than hypertension and heart diseases despite the fact that the risk of developing cardiovascular diseases is higher than osteoporosis (15).…”
Section: Discussionsupporting
confidence: 71%
“…Our findings of low composite baseline scores confirm previous data suggesting the lack of information regarding menopause provided to women. 3,4,16 The majority of subjects in our study were either premenopausal or perimenopausal. An observational study by Gallagher et al examined the relationship between women' s health characteristics and receipt of counseling regarding HRT by their health care provider.…”
Section: Ss Discussionmentioning
confidence: 99%
“…A study by Clinkingbeard et al found that almost one half of the 665 women surveyed reported leaving medical appointments with unanswered questions regarding menopause. 16 Time constraints on physicians may be a contributing factor to the lack of personalized information provided to women on this topic. The training-education session provided by pharmacists in this study was specifically designed to address the personal educational needs of each study participant.…”
Section: Ss Discussionmentioning
confidence: 99%
“…At the knowledge acquisition (KA) stage, an individual becomes aware that an innovation exists (awareness knowledge), learns what is required to use the innovation (how-to knowledge), and sometimes gathers information related to the underlying principles about how the innovation works (principle knowledge). For health professionals, the knowledge acquisition phase is frequently mediated through journal articles, the posting of new policies or procedures from an authoritative source, and through conference presentations (Fendrick, Hirth, & Chernew, 1996;Landrum, 1998); for consumers, knowledge of medical innovation may be the result of the patient-doctor encounter or information provided by printed materials or the media (Clinkingbeard, Minton, Davis, & McDermott, 1999;Jones, 1999;Newton et al,1998;Marmoreo, Brown, Batty, Cummings, & Powell, 1998).…”
Section: Diffusion Of Innovations Theorymentioning
confidence: 99%
“…Published papers are an elemental and generally trusted means by which researchers communicate to the medical community and clinicians are persuaded that research findings are important; thus, the literature can be seen to play a primary role in communicating innovative ideas and technologies between networks and can, furthermore, be viewed as a bridging tie between loosely connected groups. Published articles also play an important, though less formal role in bringing information to women: a community, mail-based survey in 1999 found that the "number one source of information about menopause was women's magazines (76%)" (Clinkingbeard et al, 1999(Clinkingbeard et al, , p. 1097; a telephone survey found that printed materials were an important source of information for 44.5% of respondents, with 59.6% of women 50-59 years of age citing the use of printed material (Newton et al, 1998); and qualitative studies confirm the central role of the popular press as a source of HT and menopause information (Griffiths, 1999;Jones, 1999). Granovetter's (1973) theory is specifically related to information flow through interpersonal ties and does not discuss communication channels such as published literature.…”
Section: Strength Of Weak Ties Theorymentioning
confidence: 99%